الحماية القضائية لألسرة في ظل التشريع الجزائري - خشعي ابراهيم بوعثمان جمال (المسيلة, 2023)
تعترب لرالطةربا لرجية ربا مرب أقربم لألنظمربا لرربي عافهرب لالنسرب ، هتربم إىل حتق رب لرسربي ةا يلالسربتقال يتيمرب أمه ته يف كوهن سبب يةود لربشايا يلستمال ه يأهم م مي ج لرعالقا طني لألزيلج ط طع لخلصوص ا يلرسايا لرذي ال يسمح رلغري ط رتمخل يف ح هتم يشؤيهنم حىت يف ح را لستفح ل لملش كل ط ةهم لألما لرذي أدى إىل تربخخا ظهربو لرعميم م لجلالئم لرجية ا. رذل فقم مةح لرق نو، لجلجلئاي سلة ت رلق ضي قصم لرتصربمي ذربذا لجلربالئم لرجية ربا كمرب مةحرب لختص صرب ت تع جل تةظ م ت تثبت لرربجيلج لرعربايف لرربذي كرب ، عربم إفاليفرب يف ط طعرب لراضربي معيربلا حق ق ربا ف تخكربم مرب تربولفا أ كرب ، لرجيلج طسم ع لرشربهود ييةتهربي طصربمي حيربم لاتبرب ت كمرب أ، فرب لرالطةربا لرجية ربا مبختلرب طاقهرب كرب رةال يلخللربع يلرتةل ربرب فقربربم يضربربع لملشربرباع مللربربا مربرب لملربربولد تةظ مربرب يحتلربرب ال لطتربربمل ل طافربربع لرربربمعوى مربرباي ل طربرب ةال لت لرصربربلح يلرتحيربرب م يمربرب هةربرب تربرب ز أمه ربربا لرق ضربربي يدي ا أتةربرب ق ربرب لرالطةربربا لرجية ربربا مربرب خربربالل مربرب يتمتربربع طربرب مربرب نصربربو يأحيربرب يلرربربي طمي ه مستممة أس س م لرشايعا لاسالم ا. summary: Marriage is considered one of the oldest systems known to man. It aims to achieve tranquility and stability. The importance of marriage lies in the reason for the existence and continuity of humanity. of marital offences. Therefore, the Algerian law granted powers to the judge in order to address these marital crimes, as well as granting him specializations dealing with regulations proving customary marriage, so it must fulfill all the pillars of marriage, which are represented in hearing witnesses and ends with the issuance of a ruling of proof, and the dissolution of the marital bond in its various ways such as divorce, divorce and divorce, The legislator has laid down a number of articles in organization and analysis, starting with the filing of the lawsuit, passing through the reconciliation and arbitration procedures. Hence, the importance of the judge and his role during the establishment of the marital bond emerges, through his texts and rulings, which in turn are derived mainly from Islamic law.
Keywords: الحماية القضائية - الألسرة - للتشريع الجزائري